Compensation, Benefits and Employee Turnover: HR Strategies for Retaining Top Talent. (May 2013) - Bryant, Phil C.; Allen, David G.
Employee turnover is recognized as costly and disruptive. The costs of employee turnover often exceed 100% of the annual salary for the vacated position. Yet managers are often unaware of the full range of tools and tactics available for effectively managing employee turnover. Based on award-winning research and professional experience, the article offers managers several strategies for effectively managing employee turnover. Strategies offered include both compensation and benefits–based solutions and solutions beyond compensation and benefits.